Faktor – Faktor yang Mempengaruhi Bioavailabilitas Besi bagi Tumbuhan - Gebhardus Djugian Gelyaman (Saintek Lahan Kering, 2018)
Iron plays an important role in plant metabolism, one of which is the forming of chloroplasts. Iron is needed in small amounts but iron deficiency can cause yellow spots on the leaves, indicating failure of chlorophyll formation or known as chlorosis. Therefore, iron becomes an essential element or micronutrients whose existence is absolute must be met by plants. Iron is very abundant in nature found in the form of minerals. However, the availability of iron for plants is very low. The availability of iron is related to the solubility of iron in soil solutions or water in nature. This paper will review factors affecting the availability of iron for plants, including the effects of soil and water pH, the role of bacteria, soil organic matter and the potential reduction of soil or water. Interaction of these factors produces a certain value of pH and reduction potential (E) in water and soil. The resulting iron specimens based on the correlation between the pH value and the environmental redox reaction value can be predicted using the pourbaix diagram of iron in water and soil.